Estimating Risk of Pituitary Apoplexy after Resection of Giant Pituitary Adenomas - Butterfield, John T.; Araki, Takako; Guillaume, Daniel; Tummala, Ramachandra; Caicedo-Granados, Emiro; Tyler, Matthew A.; Venteicher, Andrew S. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Background Pituitary apoplexy after resection of giant pituitary adenomas is a rare but often cited morbidity associated with devastating outcomes. It presents as hemorrhage and/or infarction of residual tumor in the postoperative period. Because of its rarity, its incidence and consequences remain ill defined.Objective The aim of this study is to estimate the rate of postoperative pituitary apoplexy after resection of giant pituitary adenomas and assess the morbidity and mortality associated with apoplexy.Methods A systematic review of literature was performed to examine extent of resection in giant pituitary adenomas based on surgical approach, rate of postoperative apoplexy, morbidities, and mortality. Advantages and disadvantages of each approach were compared.Results Seventeen studies were included in quantitative analysis describing 1,031 cases of resection of giant pituitary adenomas. The overall rate of subtotal resection (<90%) for all surgical approaches combined was 35.6% (95% confidence interval: 28.0–43.1). Postoperative pituitary apoplexy developed in 5.65% (n = 19) of subtotal resections, often within 24 hours and with a mortality of 42.1% (n = 8). Resulting morbidities included visual deficits, altered consciousness, cranial nerve palsies, and convulsions.Conclusion Postoperative pituitary apoplexy is uncommon but is associated with high rates of morbidity and mortality in subtotal resection cases. These findings highlight the importance in achieving a maximal resection in a time sensitive fashion to mitigate the severe consequences of postoperative apoplexy.
Keywords: pituitary adenoma; giant pituitary adenoma; pituitary apoplexy; skull base surgery; endoscopic endonasal approach